BENEFITS OF FINANCIAL RATIOS FOR FINANCING SHARIA BANKING INDONESIA - Ahmad Habibi; Muhammad Iqbal (Univeristas Islam Bandung, 2021)
This study aims at how the benefits of financial ratios to Islamic banking financing in Indonesia. The data used is time-series data. Population, as well as samples in this study, are statistical reports of sharia banking Sharia Commercial Banks in Indonesia for the period January 2015 - December 2017. Ratio selection is conducted by using a stepwise regression method as well as hypothesis testing is done by multiple regression, t-test, and F test. The results obtained from the study show that the value of Adjusted R2 can obtain values of 0.914 or 91.40%. The t-test results show that FDR, NPF, and ROA significantly influence Sharia Banking Financing. This shows that from the financial ratios used in this study, three financial ratios that affect the Financing of Sharia Banking in Indonesia, namely FDR, NPF, and CAR.